2020
DOI: 10.1016/j.cjco.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ambulatory Cardiac Monitoring Before and After Transcatheter Aortic Valve Replacement

Abstract: Remote ambulatory cardiac monitoring (rACM) could identify high-grade atrioventricular block (AVB) before and after transcatheter aortic valve replacement (TAVR). Retrospective analysis of patients undergoing TAVR, with 14-day rACM before and after TAVR, was performed. Of 62 patients undergoing TAVR, 41 patients had rACM before TAVR. Three patients had asymptomatic AVB leading to planned pacemaker (PM) implant. After TAVR, 23 patients had rACM, with 1 patient requiring a PM implant for asymptomatic AVB. Five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These results match those observed in earlier studies. 10 , 13 , 14 Anticoagulation treatment was initiated in only 1 patient with persistent Af/af, which was in line with suggestions from the 2021 Journal of the American College of Cardiology State‐of‐the‐Art Review. 8 However, the decision of when to transfer a patient to anticoagulation should be individualized given the higher score of both CHA2DS2‐VASc and HAS‐BLED.…”
Section: Discussionsupporting
confidence: 73%
“…These results match those observed in earlier studies. 10 , 13 , 14 Anticoagulation treatment was initiated in only 1 patient with persistent Af/af, which was in line with suggestions from the 2021 Journal of the American College of Cardiology State‐of‐the‐Art Review. 8 However, the decision of when to transfer a patient to anticoagulation should be individualized given the higher score of both CHA2DS2‐VASc and HAS‐BLED.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have demonstrated that a significant proportion of TAVR candidates displayed HAVB or severe bradyarrhythmia during pre-procedural ECG monitoring either with 24-h in-hospital telemetry [ 59 ] or with ambulatory systems (patch ECG recorder, mobile telemetry), allowing a prolonged (≥7 days) recording [ 60 , 61 ]. Overall, approximately 3% of patients had HAVB episodes pre-TAVR, among whom 2/3 underwent pre-procedural PPI [ 62 ].…”
Section: Unmet Needsmentioning
confidence: 99%
“…[ 33 ] Some studies have also suggested ambulatory monitoring for conduction defects and arrhythmias prior to TAVR to increase the sensitivity in detecting risk factors for HAVB which may develop after TAVR. [ 34 , 35 ]…”
Section: Timing Of Heart Blockmentioning
confidence: 99%